Proficiency testing in immunohaematology in Ontario, Canada, and in the United Kingdom: a comparative study. Issue 5 (May 1985) - Pinkerton, P H; Zuber, E D; Wood, D E; Holburn, A M; Prior, D
Abstract : A comparative study of proficiency testing models in immunohaematology has been carried out between the United Kingdom National External Quality Assessment Scheme and the Laboratory Proficiency Testing Program of the Ontario Medical Association, using material supplied by both programmes to laboratories in the United Kingdom and Ontario. The results suggest that the general standard of performance in immunohaematology practice is similar in the two jurisdictions and that, where clear differences are seen, these reflect differences in technique or in educational emphasis.